Is endoscopy a must before laparoscopic cholecystectomy? - R., Satish Kumar; Ram, Burri Mohan; C., Tejasvi Kumar; Reddy, Vamshi Krishna (International Surgery Journal, 2021)
Background: Laparoscopic cholecystectomy is common surgery performed for gall stone diseases and the gold standard procedure nowadays. But it is sometimes challenging to distinguish whether pain abdomen is due to gallstones or other UGI (upper gastro-intestinal) pathologies. Present study was conducted to rule out UGI pathologies in the patients undergoing cholecystectomy by performing UGI endoscopy as routine for effective management of the cases. The aims and objectives were to study the role of preoperative UGI endoscopy as an investigative modality to rule out UGI disorders in patients with gall stone disease. Methods: The study population consisted of 100 patients admitted for the management of gall stone diseases in KIMS hospital Bengaluru between January 2018 to July 2019. UGI endoscopy was done in all the patients routinely and to look for significant pathologies and patients with upper GI pathologies were adequately treated and later laparoscopic cholecystectomy was done. Postoperative events of pain abdomen were assessed on POD (postoperative day) 7, 14, 30, 60 days. Results: Out of the 100 patients in the study 55 patients (55%) had UGI pathologies on endoscopy and 30 patients (54.5%) are positive for H. pylori, 29 patients (52%) had persistent pain abdomen on POD 60 with p value of 0.001 which is statistically significant and 19 patients (34%) had persistent pain abdomen on POD 30 with p value <0.001 which is statistically significant. Conclusions: Beside its cost effectiveness, UGI endoscopy may potentially help in reducing the incidence of postoperative persistence of symptoms. UGI endoscopy has a vital role in the initial evaluation and investigation of patients with symptomatic gall stones.